(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2017)
The paper brings an overview of basic approaches to the concept of quality and quality management in order to improve secondary health care. We observe the concept of quality from the perspective of accreditation, categorization and certification of health institutions in the secondary health care. Quality health care is one that meets the needs of users and professional needs, achieves its goals and uses resources in the most efficient manner. Quality in health care is an example of good practice of adopting and improving standards, processes and outcomes. Improving quality requires knowledge and skills with an emphasis on lifelong learning and adjustment to patient’s needs and values. Quality is the responsibility of all individuals within the organization. Poor quality is expensive because of the inaction of people within the system. The Heath Care Quality Act has determined the principles and the system of measures for achieving and improving quality. These are the measures for achieving quality health care and the implementation of the principles of efficiency and effectiveness of the quality of health care procedures at all levels of health care, the principles of orientation to the patient as well as the principle of patient safety. The implementation of quality systems results in some new expenditures and every expense incurred is in the function of creation and production of goods and services. In medical institutions we provide health services and thus achieve income. Expenses have to be calculated into the price if we want to generate profit. Keywords: Secondary health care, concept of quality, quality improvement